EVALUASI DAMPAK PROGRAM PUSKESMAS SANTUN USIA LANJUT DI KOTA SEMARANG - Febrilia Dewi Christiani Silitonga; Sri Suwitri; Aufarul Marom (Journal of Public Policy and Management Review, 2016)
Increasing number of the elderly is not offset by the improvement of their health status. So that, elderly friendly primary health care was inisiated to realize it. Program has been going on for 6 years, but its impact has not been evaluated. The purpose of the research is to comparing the impact for the target group and group outside the target. Individu get easiness of administration and low cost treatment. Individual impacts which have not been achieved are easiness of referral submission to hospital and optimizing of elderly friendly facilities utilization. All Posyandu which are fostered by Puskesmas Mijen, Puskesmas Tlogosari Kulon, Puskesmas Bulu Lor and Puskesmas Kagok are successfully directed into strata mandiri. The impacts for the institution which have not been achieved are the realization of 70% health service coverage and availability of eldery friendly facilities in each Puskesmas. Community supports the execution of posyandu and empower the elderly in their neighborhood. The impacts which have not been achieved are home visit yet intense and nursing home never implemented. Puskesmas is suggested to facilitating the process of referral submission by helping to get the approval letter from DKK Semarang. Program have to introduced by making inscribed board, poster, also socialize it in posyandu. Addition of elderly friendly primary health care is adjusted to instituion budget per year. Puskesmas have to evaluate the implementation of the program. Kader have to actuate the home visit and cooperate with Bina Keluarga Lansia to actuate the nursing home.